Hybrid additive manufacturing of 3D electronic systems. (23rd August 2016) - Li, J; Wasley, T; Nguyen, T T; Ta, V D; Shephard, J D; Stringer, J; Smith, P; Esenturk, E; Connaughton, C; Kay, R
Abstract: A novel hybrid additive manufacturing (AM) technology combining digital light projection (DLP) stereolithography (SL) with 3D micro-dispensing alongside conventional surface mount packaging is presented in this work. This technology overcomes the inherent limitations of individual AM processes and integrates seamlessly with conventional packaging processes to enable the deposition of multiple materials. This facilitates the creation of bespoke end-use products with complex 3D geometry and multi-layer embedded electronic systems. Through a combination of four-point probe measurement and non-contact focus variation microscopy, it was identified that there was no obvious adverse effect of DLP SL embedding process on the electrical conductivity of printed conductors. The resistivity maintained to be less than 4  ×  10 −4 Ω · cm before and after DLP SL embedding when cured at 100 °C for 1 h. The mechanical strength of SL specimens with thick polymerized layers was also identified through tensile testing. It was found that the polymerization thickness should be minimised (less than 2 mm) to maximise the bonding strength. As a demonstrator a polymer pyramid with embedded triple-layer 555 LED blinking circuitry was successfully fabricated to prove the technical viability.